A dense and compact laser cladding layer with solid metallurgical bonding significantly improved corrosion resistance of Mg alloy for engineering applications. Issue 9 (16th March 2020) - Li, Sheng; Yi, Laihua; Jia, Xiao; Xiang, Dong; Liu, Tongfang; Ji, Bo
Abstract: Although Mg alloy attracts great attention for engineering applications because of high specific strength and low density, low corrosion resistance limits its extensive use. In this study, Mg–Al–Zn–Mn alloy was treated via a laser cladding process to generate a dense and compact laser cladding layer with solid metallurgical bonding on the substrate for improving corrosion resistance, effectively hindering the corrosion pervasion into Mg alloy. The corrosion current density declined from 103 μA/cm 2 for Mg alloy to 13 μA/cm 2 for the laser cladding layer in NaCl aqueous solution. Moreover, the laser cladding layer was slightly corroded in comparison with Mg alloy in NaCl aqueous solution. Besides, the microhardness of the cladding layer reached a mean value of 170.5 HV, 3.1 times of Mg alloy (56.8 HV) due to the in situ formation of hardening intermetallic phases. Wear resistance of laser cladding layer was also obviously improved. These results demonstrated that the laser cladding layer obviously enhanced anticorrosion property of Mg alloy for engineering applications. Abstract : An Al/Si eutectic layer was prepared on Mg alloy substrate via a laser cladding process and a dense and compact laser cladding layer with solid metallurgical bonding significantly improved corrosion resistance of Mg alloy.